2015
DOI: 10.1109/jmems.2015.2470132
|View full text |Cite
|
Sign up to set email alerts
|

The Piezoresistive Effect of SiC for MEMS Sensors at High Temperatures: A Review

Abstract: This article has been accepted for inclusion in a future issue of this journal. Content is final as presented, with the exception of pagination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
162
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 222 publications
(163 citation statements)
references
References 130 publications
(199 reference statements)
1
162
0
Order By: Relevance
“…Paper 4 was an extension of the study from Paper 3 where we included the adsorption of SiH, SiH2, SiX, SiHX, SiX2 for X being F, Cl and Br. Also, both the C-face and the Si-face were considered.…”
Section: Chapter 4 Results and Summarymentioning
confidence: 99%
See 3 more Smart Citations
“…Paper 4 was an extension of the study from Paper 3 where we included the adsorption of SiH, SiH2, SiX, SiHX, SiX2 for X being F, Cl and Br. Also, both the C-face and the Si-face were considered.…”
Section: Chapter 4 Results and Summarymentioning
confidence: 99%
“…The study was performed using the same cluster as in Paper 4 and the adsorption was assumed to occur with correct stoichiometry as before. The gaseous hydrocarbon species included in the study were C2H2, C2H4, CH3 and CH4.…”
Section: Chapter 4 Results and Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…[32][33][34][35][36] A comprehensive review on the applications of the piezoresistance of SiC can be found in ref. [37] As show in Figure 4c, the linear current voltage (I-V) characteristic of the 94 nm SiC membrane indicates the good Ohmic contact between Ni and SiC. Next, a constant voltage was applied to the SiC resistors, while the output current was monitored under applied pressure using Agilent B4105, Figure 4d.…”
Section: à3mentioning
confidence: 98%